2019
DOI: 10.1002/uog.20276
|View full text |Cite
|
Sign up to set email alerts
|

Late‐stage Cesarean section causes recurrent early preterm birth: how to tackle this problem?

Abstract: About 500 000 preterm deliveries before 37 weeks' gestation occur annually in the USA. Worldwide, this figure is estimated to be 15 million each year, with serious associated health implications and high costs to families and society. The management and prevention of preterm birth is highly variable depending on the etiology. Recent studies have shown that Cesarean section (CS) performed late in labor or at full dilatation (FDCS) is associated with recurrent early preterm birth and late miscarriage. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Intrapartum emergency CD are more likely to involve the cervix cervical tissue 31,32 and the risk increases as labour progressed and the lower segment is further stretched by the descent of the fetal presentation. 33,34 As the labour progresses, full cervical effacement causes the smooth muscle of the internal sphincter to migrate into the lower uterine segment 35 making it difficult for the surgeon to localise the upper cervix. This can explain the higher incidence of scars and niches below the vesicovaginal fold in the subgroup who had an emergent CD at > 4 cm in the present study (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Intrapartum emergency CD are more likely to involve the cervix cervical tissue 31,32 and the risk increases as labour progressed and the lower segment is further stretched by the descent of the fetal presentation. 33,34 As the labour progresses, full cervical effacement causes the smooth muscle of the internal sphincter to migrate into the lower uterine segment 35 making it difficult for the surgeon to localise the upper cervix. This can explain the higher incidence of scars and niches below the vesicovaginal fold in the subgroup who had an emergent CD at > 4 cm in the present study (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the cervical morphology during CD performed late in labor may contribute to preterm birth in subsequent pregnancies. 4,6,36 Recent data have indicated that the uterine cervix is made a specialized sphincter at the internal os and the cervical smooth muscle cells may play a role in cervical remodeling as well as initiating and/or disseminating uterine contractility. 38 We found that women who had an emergency CD at cervical dilatation >4 cm presented with a significantly higher incidence of both their scar or a niche to be located below the vesicovaginal fold (Table 2), suggesting that this subgroup of women could be at higher risk of premature delivery in subsequent pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…When the CD was performed at a cervical dilatation ≤4 cm, there was a significantly ( P = .012) higher incidence of a uterine niche located above the vesicovaginal fold and a significantly ( P = .0002) lower proportion of cesarean scar below the vesicovaginal fold compared with those who had their CD at active stage of labor. Intrapartum emergency CD is more likely to involve the cervix cervical tissue 33,34 and the risk increases as labor progressed and the lower segment is further stretched by the descent of the fetal presentation 35,36 . As the labor progresses, full cervical effacement causes the smooth muscle of the internal sphincter to migrate into the lower uterine segment, 37 making it difficult for the surgeon to localize the upper cervix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations